Are pre-terms born timely and right immunized? Results of an Italian cohort study. Issue 6 (3rd June 2018) - Laforgia, Nicola; Di Mauro, Antonio; Bianchi, Francesco Paolo; Di Mauro, Federica; Zizzi, Andrea; Capozza, Manuela; Intini, Silvia; Gallone, Maria Serena; Tafuri, Silvio
ABSTRACT: The aim of this study is to evaluate the vaccination coverage at 24 months of chronological age in a sample of preterm infants discharged by the Neonatal Intensive Care Unit (NICU) of the Bari Policlinico University General Hospital in Italy. The list of infants preterm born discharged during 2013 by the NICU was obtained by hospital database. Vaccination status of each subject at 24 months of chronological age was acquired by the Apulian Regional Vaccination Register (GIAVA). 159 preterm borns were enrolled in this study. 98.1% received the 1st dose of hexavalent vaccine and 98.7% the 1st dose of pneumococcal conjugate vaccine. The 8.8% of hexavalent vaccinations were performed during hospitalization. The percentage of immunized subjects decreased to 91.2% and 87.3% for the 2nd and 3rd dose of hexavalent vaccine and to 90.6% and 86.1% for the 2nd and 3rd dose of pneumococcal conjugate vaccine. Coverage for MMR, MEN C and Varicella vaccines were, respectively 76.4%, 86.0% and 80.9%. Pre-terms received the vaccinations later than the age recommended by public health guidelines. Age at the immunization, for all vaccines, seems to increase for lower gestational age and birth weight and for higher length of hospitalization. This study shows a high risk of vaccine delay among pre-terms born. There is a strong need to improve specific vaccination strategies for this group. Neonatologists might play a key role in informing parents about the vaccination schedule at the moment of NICU discharge and during follow-up, also preparing correct time schedule.